THE SEMIOTIC SIGNS ON CHAPTER COVERS IN THE GRAPHIC NOVEL MAUS: “A SURVIVOR’S TALE” BY ART SPIEGELMAN - ALFATIH, MUHAMMAD FAIZ (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: semiotics, sign, code, chapter cover, graphic novel, Maus. Language is important in daily life because people need to communicate withone another in their society. A sign is another way to communicate among each other. In order to do that, visual signs may be used which contain some pictures with a special meaning to express the messages through the signs in the illustrative pictures such as chapter cover in the graphic novel. Meanwhile, a sign will have no meaning without codes inside it. The writer conducted a study about the semiotic analysis on chapter cover in the graphic novel Maus: A Survivor’s Tale by Art Spiegelman based on Peirce’s triadic theory and Codes theory by Chandler. There are two problems solved, namely: (1) What symbol, icon, and index on chapter covers of the graphic novel Maus: A Survivor’s Tale by Art Spiegelman are, and (2) What kinds of codes are used in interpreting the meaning of signs of the chapter cover in the graphic novels Maus: A Survivor’s Tale by Art Spiegelman are. This study uses qualitative approach since the data are not in the forms of numbers or statistic calculation. The writer conducts the content or document analysis to analyze the signs and the codes used in chapter cover of the graphic novel Maus: A Survivor’s Tale by Art Spiegelman. There are six chapter covers in the graphic novel Maus and the writer chooses all of chapter covers, namely The Sheik, The Honeymoon, The Prisoner of War, The Noose Tightens, Mouse Holes and Mouse Trap.This study reveals that some signs represent the content of the graphic novel. In the chapter cover, symbols, icons, and indexes in the first chapter cover and symbols, icons, and indexes in the second chapter cover are found. From the third to the sixthchapter cover also, symbols, icon, and indexes based on Peirce’s the mode theory arefound. Meanwhile, there are codes proposed by Chandler.  The codes found are socialcodes such as verbal language, the bodily codes, commodity codes, textual codes, and interpretative codes.The writer suggests the Faculty of Cultural Studies, Universitas Brawijaya give more references related to semiotics studies. The writer also suggests the next researcher broaden the semiotics scope and analyze the other objects.